Chromatin remodeling and epigenetic regulation in chronic kidney disease - Liang, Jinzi; Wan, Chao (Frontiers in Genetics, 2026)
The progression of chronic kidney disease (CKD) stems from persistent maladaptive alterations in renal cellular gene expression, processes governed by dynamic epigenetic regulation. The dynamic regulation of chromatin encompasses structural changes, condensation, altered accessibility, and ATP-dependent remodeling, playing a pivotal role in CKD progression. Dysregulation of these processes is increasingly implicated in key pathogenic events such as fibroblast activation and inflammatory responses. Recent advances in multi-omics approaches have provided crucial insights into the composition, mechanisms, and dysregulation of chromatin states within diseased kidneys. In this review, we summarize the current understanding of chromatin dynamics and remodeling in CKD, emphasizing their role in disease progression and their interplay with other epigenetic layers. We further discuss how these mechanisms contribute to establishing pathogenic transcriptional memory and highlight emerging therapeutic opportunities.